Intriguing Effects of Halogen Substitution on the Photophysical Properties of 2,9-(Bis)halo-Substituted Phenanthrolinecopper(I) Complexes - Brown-Xu, Samantha; Fumanal, Maria; Gourlaouen, Christophe; Gimeno, Lea; Quatela, Alessia; Thobie-Gautier, Christine; Blart, Errol; Planchat, Aurélien; Riobé, François; Monnereau, Cyrille; Chen, Lin X; Daniel, Chantal; et al. (Inorganic chemistry, 2019)
Three new copper(I) complexes [Cu(L ) ] (PF ) (where L stands for 2,9-dihalo-1,10-phenanthroline and X = Cl, Br, and I) have been synthesized in order to study the impact of halogen substituents tethered in the α position of the chelating nitrogen atoms on their physical properties. The photophysical properties of these new complexes (hereafter named Cu-X) were characterized in both their ground and excited states. Femtosecond ultrafast spectroscopy revealed that early photoinduced processes are faster for Cu-I than for Cu-Cl or Cu-Br, both showing similar behaviors. Their electronic absorption and electrochemical properties are comparable to benchmark [Cu(dmp) ] (where dmp stands for 2,9-dimethyl-1,10-phenanthroline); furthermore, their optical features were fully reproduced by time-dependent density functional theory and ab initio molecular dynamics calculations. All three complexes are luminescent at room temperature, showing that halogen atoms bound to positions 2 and 9 of phenanthroline are sufficiently bulky to prevent strong interactions between the excited Cu complexes and solvent molecules in the coordination sphere. Their behavior in the excited state, more specifically the extent of the photoluminescence efficiency and its dependence on the temperature, is, however, strongly dependent on the nature of the halogen. A combination of ultrafast transient absorption spectroscopy, temperature-dependent steady-state fluorescence spectroscopy, and computational chemistry allows one to gain a deeper understanding of the behavior of all three complexes in their excited state.